(NbIBLIOTEKA (B"(NoGONEK(B". (NzARUBEVNAQ KLASSIKA (B/ s - (NbAJRON(B, (NdVORDV gORDONs ((NmOSKWA(B: s (NpRAWDA(B, s, 1981)
(Nw sOBRANII PREDSTAWLENY PEREWODY PROIZWEDENIJ bAJRONA(B, (NSDELANNYE WYDA@]IMISQ RUSSKIMI PO\TAMI I PISATELQMI (B- (NvUKOWSKIM(B, (NlERMONTOWYM(B, (Na(B.(Nk(B.(NtOLSTYM(B, (NtURGENEWYM(B, (NbLOKOM(B, (NbUNINYM(B, (NIZWESTNYMI SOWETSKIMI PO\TAMI (B- (NpASTERNAKOM(B, (NmAR[AKOM(B, (NlUGOWSKIM(B, (NA TAKVE PEREWOD^IKAMI(B-(NBAJRONISTAMI (B- (N{ENGELI(B, (NgNEDI^(B, (NlEWIKOM(B.s
rus
Keywords: (NpO\ZIQ(B, (NPO\MYs; (NsTIHOTWORENIQs; (NdRAMAs; (NsATIRAs -- (NpROZAs -- (NtRAGEDIQs